Rekrutmen dan Seleksi Tenaga Pendidik dan Kependidikan : Studi Literatur Sistematis dengan Prisma - Umam, Khairul; Afina Fidaroin Naja; Arie Wahyu Maulidya; Syunu Trihantoyo; Muhammad Sholeh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze optimal strategies in the selection and recruitment process of educators and academic staff to enhance the quality of education. The research employs a literature review method using the PRISMA approach, which facilitates a systematic screening of relevant scholarly articles. The findings indicate that an effective selection process involves a combination of interviews, competency tests, and assessments based on validity and reliability. Additionally, recruitment can be conducted through centralized or decentralized approaches, depending on institutional needs. The key selection criteria for educators include academic qualifications, experience, communication skills, technological competence, professionalism, and alignment with the institutions vision and mission. By implementing a rigorous and data-driven selection system, educational institutions can improve efficiency in acquiring high-quality personnel and support sustainable educational development. Keywords: Recruitment, Selection, Educator and Academic Staff